Francis Wade correspondence - Wade, Francis
ALS written by Wade to John Swanwick relating to personal debts incurred by Wade on behalf of the U.S. government while he served as a quartermaster during the Revolution.
Continental Army officer and quartermaster general.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Swanwick, John, -- 1740-1798 -- Correspondence; United States. -- Continental Army; Debt; Quartermasters; United States -- History -- Revolution, 1775-1783 -- Finance; Army officers